AlN/nitrided sapphire and AlN/non-nitrided sapphire hetero-structures epitaxially grown by pulsed laser deposition: A comparative study. (September 2017) - Luo, Jianghua; Wang, Wenliang; Zheng, Yulin; Li, Xiaochan; Li, Guoqiang
Abstract: AlN/nitrided sapphire and AlN/non-nitrided sapphire hetero-structures epitaxially grown by pulsed laser deposition (PLD) have been carried out. The characterizations find that when the nitridation process is implemented on sapphire substrates, the properties of AlN/sapphire hetero-structures are improved significantly. It is also identified that very smooth AlN surface with the root-mean-square surface roughness of 1.5 nm, full-width at half-maximums for AlN(0002) and AlN(10–12) X-ray rocking curves of 0.59°and 0.91°. Abrupt AlN/sapphire hetero-interfaces are obtained in AlN/nitrided sapphire hetero-structures. These high-quality AlN/nitrided sapphire hetero-structures shed light for the fabrication of highly-efficient AlN/nitrided sapphire-based devices. Highlights: High-quality AlN/ nitrided sapphire hetero-structures have been grown by PLD. Effect of sapphire substrate nitridation on the properties of AlN is carefully studied. Sharp and abrupt AlN/sapphire hetero-interfaces have been obtained by the nitridation of sapphire substrate.